2016
DOI: 10.4236/ojog.2016.613099
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Nitric Oxide (NO) and Corticotrophin Releasing Hormone (CRH) between Normal Pregnancy and Preeclampsia

Abstract: Preeclampsia is still a major cause of maternal death in pregnancy which needs efforts to prevent and early detection. Nitric oxide and Corticotrophin Releasing Hormone has an important role in the pathogenesis of preeclampsia to determine differences in concentrations of NO and CRH in normal pregnancy and preeclampsia, as well as to study the correlation both on the incidence of preeclampsia. This is a cross sectional study. Blood samples obtained from patients with preeclampsia (30 samples) and normal pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Recent studies revealed that CRH level has negative correlation with the length of gestation and leads to preterm birth 9 . CRH plays vital role in pathogenesis of pre-eclampsia 10 . Increased levels of CRH affects CRH-R receptors, CRH-R receptor can be used as a biomarker for prediction of preeclampsia 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that CRH level has negative correlation with the length of gestation and leads to preterm birth 9 . CRH plays vital role in pathogenesis of pre-eclampsia 10 . Increased levels of CRH affects CRH-R receptors, CRH-R receptor can be used as a biomarker for prediction of preeclampsia 11 .…”
Section: Introductionmentioning
confidence: 99%